實作為基礎的師培環境教育課程之研究 A study of Practice-based Pre-service Teacher Training of an Environmental Education Curriculum - 王順美 Shun-Mei Wang (National Changhua University of Education, 2020)
環境的危機，促使我國訂定環境教育法，早在九年一貫課程及 108 年開始實施十二年國民基本教育課程綱要，都將環境教育列為重大議題。環境教育在師培學程屬於「教育議題」的一科，然而過去師範院校以及教師法改制後的師資培育學程，很少開設環境教育。 教師能力不足往往是推動學校環境教育的障礙之一，許多國家積極在師培放入環境教育課程，臺灣近年亦鼓勵開設。本研究基於 2016、2017，研究者在國立臺灣師範大學師資培育學程教育議題類，開設的環境教育選修課程，進行教學及探討。此課程運用現實環境、生活情境，引導師資生來發展教案、試教、教師課後反思。這兩年各有 27 位及 31位師資生選修此課程，透過問卷調查、反思心得及作業、觀課紀錄、檢討，研究者發現 修課者在課程後環境素養分數提升，對於學習對象、課程設計流程更多的認識。研究者也看到課程中，修課者察覺現實情境中的環境議題敏銳度不足，需更多的說明及引導；修課者容易搞混六大類的環境內涵，需要授課者舉例說明及澄清，協助他們發展合適的教學活動。另外，本研究也發現師資生的科系及教育學程修課多寡，會影響他們將環境內涵轉化為教學活動的效能。 The crisis of the environment has pushed Taiwan to formulate The Environmental Education Act in 2010, making environmental education one of the major issues in school education. In the past, teacher training colleges and teachers' training courses rarely offered environmental education. Inadequate teacher capacity is often one of the obstacles for promoting environmental education in schools. Many countries are actively instituting environmental education courses in the program of teacher training in recent years, including Taiwan, but one of the major barriers is teachers' insufficient ability for implementing environmental education in campus. This study was conducted during 2016 and 2017 in a practice-based environmental education course for pre-service teachers. Twenty-seven and thirty-one students took the course in the two years, respectively. The goal is to explore students' learning process and results through questionnaires, class observations, and assignments. The results of the questionnaire show that students' environmental literacy scores have increased, but it is still difficult for students to be aware of an environmental issue and to identify the relevant concepts from their daily living place for curriculum design. The students need many examples from the instructors to assist in clarifying the content of six categories of environmental education programs. The study found that the specific major and education courses students took influence their teaching efficacy at transcribing environmental content to environmental activities.